Implementation of the plasma MYCN/NAGK ratio to detect MYCN amplification in patients with neuroblastoma. Issue 11 (18th September 2020) - Su, Yan; Wang, Lijun; Zhao, Qian; Yue, Zhixia; Zhao, Wen; Wang, Xisi; Duan, Chao; Jin, Mei; Zhang, Dawei; Chen, Shenglan; Yin, Jianfeng; Qiu, Lihua; et al.
Abstract : Detection of amplification of the MYCN gene is essential for determining optimal treatment and estimating prognosis of patients with neuroblastoma (NB). DNA FISH with neuroblastoma tissues or patient‐derived bone marrow cells is the standard clinical practice for the detection of MYCN amplification. As tumor cells may often be unavailable, we developed a method to detect MYCN amplification in the plasma of patients with neuroblastoma. Taking single‐copy NAGK DNA as reference, we used real‐time quantitative PCR (qPCR) to determine the MYCN / NAGK ratio in the plasma of 115 patients diagnosed with NB. An increased MYCN / NAGK ratio in the plasma was consistent with MYCN amplification as assessed by DNA FISH. The AUC for a MYCN / NAGK ratio equal to 6.965 was 0.943, with 86% sensitivity and 100% specificity. Beyond the threshold of 6.965, the MYCN / NAGK ratio correlated with a heavier tumor burden. Event‐free and overall survival of two years were significantly shortened in stage 4 patients with a MYCN / NAGK ratio higher than 6.965. Plasma MYCN / NAGK ratios increased in patients with progressive disease and relapse. Thus, we conclude that the determination of the plasma MYCN / NAGK ratio by qPCR is a noninvasive and reproducible method to measure MYCN amplification in patients with NB. Abstract : Detection of amplification of the MYCN gene is essential for estimating treatment and prognosis of patients with neuroblastoma. We developed a method to detect MYCN amplification using the plasma DNA by quantitative PCR. An increase in MYCN copies in the plasma was consistent with MYCN amplification as assessed by DNA‐FISH to measure MYCN amplification in patients with neuroblastoma.